Les attitudes diverses des néoplatoniciens au sujet de la théurgie - Hadot, Ilsetraut (Hyperboreus, 2017)
This paper discusses the attitudes of the Neoplatonist philosophers of the 3rd to 6th centuries AD toward theurgy, i.e., the conglomerate of different magical techniques and ritual rites used to communicate with gods. All this time there were persons who rejected theurgy as it was propagated by Iamblichus in his De mysteriis or assigned to it only a subordinate role in the salvation of the human soul in comparison with philosophy. Only a few Neoplatonists, however, rejected theurgy entirely; much more often they rejected only those theurgic techniques that Iamblichus had added to the traditional cultic rites, viz. those that could not be practically distinguished from magic rites. Persons like Eusebius of Myndes, who were not able to believe in wonders, tried to expose the frauds of charlatans. Depending on their attitudes toward theurgy, the Neoplatonists estimated the role of philosophy differently: some, following Iamblichus, assigned to theurgy a higher status than philosophy; others treated them as having equal value; and a third group preferred rational philosophical enquiry to theurgy. But the overwhelming majority of the Neoplatonists, including Iamblichus himself, considered the study of philosophy indispensable; according to the Neoplatonists (and also to Iamblichus), the salvation of the soul was available only to a minority.